Outcomes of Two Trials of Oxygen-Saturation Targets in Preterm Infants - Tarnow-Mordi, William; Stenson, Ben; Kirby, Adrienne; Juszczak, Edmund; Donoghoe, Mark; Deshpande, Sanjeev; Morley, Colin; King, Andrew; Doyle, Lex W; Fleck, Brian W; Davis, Peter G; Halliday, Henry L; et al. (The New England journal of medicine, 2016)
In two trials involving preterm infants, an oxygen-saturation target of 85 to 89% versus 91 to 95% resulted in nonsignificantly higher rates of death or disability at 2 years but in significantly increased risks of the combined outcome and of death alone in post hoc combined analyses. The determination of the range of oxygen saturation that minimizes the competing risks of death, retinopathy of prematurity, and later disability in preterm infants is important. 1 , 2 The U.K. and Australian Benefits of Oxygen Saturation Targeting (BOOST)–II trials are two of five comparative effectiveness trials of the targeting of oxygen saturation in infants born before 28 weeks’ gestation. 3 – 8 These trials, known collectively as the Neonatal Oxygen Prospective Meta-analysis (NeOProM) Collaboration, were designed to compare the effects of a lower oxygen-saturation target range (85 to 89%) versus a higher target range (91 to 95%) on a primary outcome of death . . .